Th2 Modulation of Transient Receptor Potential Channels: An Unmet Therapeutic Intervention for Atopic Dermatitis - Meng, Jianghui; Li, Yanqing; Fischer, Michael J. M.; Steinhoff, Martin; Chen, Weiwei; Wang, Jiafu (Frontiers in Immunology, 2021)
Atopic dermatitis (AD) is a multifaceted, chronic relapsing inflammatory skin disease that affects people of all ages. It is characterized by chronic eczema, constant pruritus, and severe discomfort. AD often progresses from mild annoyance to intractable pruritic inflammatory lesions associated with exacerbated skin sensitivity. The T helper-2 (Th2) response is mainly linked to the acute and subacute phase, while Th1-responses have been associated in addition with the chronic phase. IL-17 and IL-22, TSLP and IL-31 also play a role in AD. Transient receptor potential (TRP) cation channel play a significant role in neuroinflammation, itch and pain indicating neuroimmune circuits in AD. However, the Th2-driven cutaneous sensitization of TRP channels is underappreciated. Emerging findings suggest that critical Th2-related cytokines cause potentiation of TRP channels, thereby exaggerating inflammation and itch sensation. Evidence involve: (i) IL-13 enhances TRPV1 and TRPA1 transcription levels; (ii) IL-31 sensitizes TRPV1 via transcriptional and channel modulation, and indirectly modulates TRPV3 in keratinocytes; (iii) The Th2-cytokine TSLP increases TRPA1 synthesis in sensory neurons. These changes could be further enhanced by other Th2 cytokines, including IL-4, IL-25 and IL-33, which are inducers for IL-13, IL-31 or TSLP in skin. Taken together, this is the first review highlighting that Th2 cytokines potentiate TRP channels through diverse mechanisms under different inflammatory and pruritic conditions, and link this effect to distinct signalling cascades in AD. This review strengthens the notion that interrupting Th2-driven modulation of TRP channels will inhibit transition from acute to chronic AD, thereby aiding the development of effective therapeutics and treatment optimization.